2021
DOI: 10.3390/molecules26144243
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Monoclonal Antibody and Development of Indirect Competitive Enzyme-Linked Immunosorbent Assay and Fluorescence-Linked Immunosorbent Assay for Detecting 3-Amino-5-methylmorpholino-2-oxazolidinone (AMOZ) in Edible Animal Tissue

Abstract: To monitor the illegal used of furaltadone, a highly sensitive indirect competitive enzyme-linked immunosorbent assay (ic-ELISA) and fluorescence-linked immunosorbent assay (FLISA) based on a monoclonal antibody (mAb) were developed for the detection of 3-amino-5-methylmorpholino-2-oxazolidinone (AMOZ), the major metabolite of furaltadone in animal tissues. The highly specific mAb, which was very sensitive to a nitrophenyl derivative of AMOZ (2-NP-AMOZ) with IC50 values of 0.11 and 0.09 ng/mL for ic-ELISA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…At the same time, there are discrete capping agents and different functional groups on its surface, thus increasing the sensitivity of the method ( Biranje et al, 2021 ). Xie et al ( Xie et al, 2021 ) established both ic-ELISA and Fluorescence-Linked Immunosorbent Assay (FLISA) based on QDs to detect AMOZ. The IC 50 values of ic-ELISA and FLISA were 0.11 and 0.09 μg/L, respectively, the recovery rate is 81.1–105.3%, and the coefficient of variation was 4.7–9.8%.…”
Section: Research Progress Of Immunosensorsmentioning
confidence: 99%
“…At the same time, there are discrete capping agents and different functional groups on its surface, thus increasing the sensitivity of the method ( Biranje et al, 2021 ). Xie et al ( Xie et al, 2021 ) established both ic-ELISA and Fluorescence-Linked Immunosorbent Assay (FLISA) based on QDs to detect AMOZ. The IC 50 values of ic-ELISA and FLISA were 0.11 and 0.09 μg/L, respectively, the recovery rate is 81.1–105.3%, and the coefficient of variation was 4.7–9.8%.…”
Section: Research Progress Of Immunosensorsmentioning
confidence: 99%
“…19−21 Previous literature reported that FLD is highly unstable in vivo and can be rapidly metabolized in the forms of 3-amino-5morpholinomethyl-2-oxazolidinone, 1-aminohydantoin, 3amino-2-oxazolidinone, and semicarbazide. 22,23 It has the potential to bind to tissue proteins with high affinity and generate long-lasting protein conjugates. 24 FLD and its metabolites can cause potential carcinogenic, mutagenic, and teratogenic effects on all living organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Previous literature reported that FLD is highly unstable in vivo and can be rapidly metabolized in the forms of 3-amino-5-morpholinomethyl-2-oxazolidinone, 1-aminohydantoin, 3-amino-2-oxazolidinone, and semicarbazide. , It has the potential to bind to tissue proteins with high affinity and generate long-lasting protein conjugates . FLD and its metabolites can cause potential carcinogenic, mutagenic, and teratogenic effects on all living organisms. , Due to the negative impact on humans and the environment, FLD has been strictly prohibited in the United States (Register, 2002), China (Regulation of Department of Agriculture of China, 2002), European Union (EU Council Regulation No.…”
Section: Introductionmentioning
confidence: 99%